Saving the Lost Melodies: Community-Based Documentation of Gambang Kromong Intangible Cultural Heritage - Riyan Adi Putra; Haykal Rizky Adam (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose This study aims to critically examine the documentation processes of the Gambang Kromong intangible cultural heritage and to analyze the operational constraints faced by a grassroots movement, specifically the Tukang Tabuh Community. Method This research adopts a qualitative approach utilizing a case study design. Primary data were collected from three key informants through semi-structured in-depth interviews, participant observation, and documentary analysis. The validity of the data was rigorously established using both methodological and source triangulation. Results/findings The findings reveal that the community successfully transitioned from static live recording methods to an active digital audio engineering methodology using a track-by-track technique, complemented by historically valid visual curation. Furthermore, significant operational constraints—including cognitive